Operation of a commercial district integrated energy system considering dynamic integrated demand response: A Stackelberg game approach. (1st July 2023) - Tan, Jinjing; Li, Yang; Zhang, Xiaoping; Pan, Weiqi; Ruan, Wenjun
Abstract: To facilitate energy coupling and coordinate distributed resources economically, this paper proposes an operation model of a district integrated energy system (IES) with a Stackelberg game approach. In the proposed model, a dynamic integrated demand response (IDR) mechanism is designed. The scenario theory is utilized to model uncertainties and the conditional value at risk (CVaR) method is employed to capture the risks of uncertainties. The district energy operator (DEO) is a common leader, while the building prosumers (BPs) and the electric vehicle aggregator (EVA) are followers. Each participant pursues the maximization of their personal benefits. Regarding the business mode, two aspects are innovative in the paper. Firstly, the relation between risk sources and risk bearers is defined. Secondly, the economic benefits of participants are guaranteed by diverse business channels. The paper demonstrates the existence and uniqueness of the Stackelberg equilibrium (SE), which is achieved by employing a bisection-based distributed algorithm. Finally, the case study of a commercial district verifies the effectiveness of the algorithm, and shows the merits of the proposed operation model, including the good benefits of all participants, as well as the significant effects of IDR programs. Highlights: The uncertain factors that affect the IES are comprehensively studied. The relation between risk sources and risk bearers is defined. A dynamic IDR mechanism is designed to make the adjustable ranges more realistic. A bisection-based distributed algorithm is proposed to obtain the equilibrium. The participants' profitability is promoted via employing diverse business channels.